A conceptual framework for understanding rebound effects with renewable electricity: A new challenge for decarbonizing the electricity sector. (October 2021) - Galvin, Ray; Dütschke, Elisabeth; Weiß, Julika
Abstract: We develop a conceptual framework for investigating rebound effects that occur consequent to increases in renewable electricity generation and use. This is vitally important due to countries' emerging commitments to decarbonize economies through sector-coupling and strategies such as the large-scale use of "green" hydrogen produced by electrolysis from renewable electricity. Rebound effects have been extensively studied in relation to energy efficiency, where they represent shortfalls in the achievement of expected energy savings after efficiency upgrades. We identify four clear elements that are essential to rebound studies to date: (a) an energy efficiency increase; (b) an associated shortfall in energy savings; (c) a clear chain of cause-and-effect from (a) to (b); and (d) a transparent, policy-useful means of quantifying the rebound effect. Our contribution to the literature is that we transfer this schema to the domain of renewable electricity, focusing on "an increase in renewable energy" for (a) and appropriate modifications to (b), (c) and (d). We offer this schema as a useful framework for research moving forward into rigorous and detailed investigation of rebound effects in the domain of renewable electricity.